Developing Panel Data and Time Series Application (DELTA) : Smoothing Module - siti mariyah; Nensi Fitria Deli (Pusat Penelitian dan Pengabdian Masyarakat Politeknik Statistika STIS, 2016)
Smoothing is commonly used methods to predict time series data. There are many applications that help in the processing of time series data that provide smoothing function such as EViews, Minitab, Zaitun TS, and R. However, these applications have some shortcomings such as the difficulty in comparing several methods. In this study, we build an open source application that provides more complete smoothing method and a facility for comparing several methods, namely smoothing module in DELTA application. Based on the tests, it can be proved that this application is suitable for users and the displayed output is consistent with the theory.